2022
DOI: 10.1371/journal.pone.0273197
|View full text |Cite
|
Sign up to set email alerts
|

Advanced practice providers versus medical residents as leaders of rapid response teams: A 12-month retrospective analysis

Abstract: Purpose In a time of worldwide physician shortages, the advanced practice providers (APPs) might be a good alternative for physicians as the leaders of a rapid response team. This retrospective analysis aimed to establish whether the performance of APP-led rapid response teams is comparable to the performance of rapid response teams led by a medical resident of the ICU. Material and methods In a retrospective single-center cohort study, the electronic medical record of a tertiary hospital was queried during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Although several studies have been performed to assess differences in the level of technical and non-technical skills of APPs, it remains difficult to establish the specific individual contribution of an APP’s performance to the combined outcome of a complex multidisciplinary process of care. Previous studies suggested that this topic should be analyzed in prospective studies using more sophisticated statistical methods [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have been performed to assess differences in the level of technical and non-technical skills of APPs, it remains difficult to establish the specific individual contribution of an APP’s performance to the combined outcome of a complex multidisciplinary process of care. Previous studies suggested that this topic should be analyzed in prospective studies using more sophisticated statistical methods [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Professional roles included in these studies varied widely but commonly included physicians, advanced practice providers, critical care nurses, and respiratory therapists. [9][10][11] The composition of RRTs in practice varies widely, and more research is needed to understand what is the optimal team composition, which will assist with achieving consistent patient outcomes. 12 Another component of rapid response systems and part of the afferent limb that has been studied are early warning systems.…”
mentioning
confidence: 99%
“…Multiple studies have addressed the areas of team composition of RRTs (efferent limb) including studies that examined different models of not only who was included but also who took lead. Professional roles included in these studies varied widely but commonly included physicians, advanced practice providers, critical care nurses, and respiratory therapists 9-11 . The composition of RRTs in practice varies widely, and more research is needed to understand what is the optimal team composition, which will assist with achieving consistent patient outcomes 12 …”
mentioning
confidence: 99%